Effectiveness of aftercare program for suicide ideators: Real-world evidence from National Suicide Surveillance System in Taiwan. Issue 42 (21st October 2022) - Siu, Wing Hin Stanford; Juang, Yeong-Yuh; Huang, Tsuei-Mi; Lin, Sheue-Rong; Chung, Chia-Chi; Tu, Hui-Tzu; Chen, Wei-Min; Wang, Bi-Hwa; See, Lai-Chu
Abstract : Aftercare programs' effectiveness for suicide ideators has seldom been reported. This study assessed rates and factors related to the recurrence of suicide-related episodes after the index suicidal ideation episode, index cases, and family members receiving aftercare. This is a secondary data analysis of 1787 suicidal ideation episodes from 1557 individuals reported to the National Suicide Surveillance System in New Taipei City, Taiwan, from January 2012 to June 2013 and followed up until September 2013. Among 1787 index suicidal ideations, 19.1% had recurrences of suicide-related episodes, including suicidal ideation (11.9%), attempt (6.7%), and death (0.5%) within 2 years after index ideation. These recurrences were significantly reduced after the index cases received aftercare twice, three, and four or higher. Family members receiving aftercare twice or more were associated with reduced suicidality in the index cases. Receiving aftercare among index cases was associated with being a woman, suicide due to occupation/finance, and reporting from suicide hotlines. Receiving aftercare among family members was associated with the index cases aged ≤ 19 years old, suicide reasons related to school, occupation/finance, and reporting from schools and hospitals. Aftercare programs for suicide ideators and family members of adolescent suicide ideators (aged ≤ 19 years old) decreased subsequent episodes of suicidal behavior.